Tissue Engineering - Hauser, Hansjörg.; Hauser, Hansjörg.; Fussenegger, Martin M.; Fussenegger, Martin M. (Methods in Molecular Medicine,, 2007)
Over the past decade, tissue engineering has spread in importance in fields as distinct as biotechnology, biopharmaceutical manufacturing, chemical engineering, cell biology, developmental biology, gene therapy, medical sciences and organic chemistry. In Tissue Engineering, 2nd Edition, a team of experts from these various disciplines share recent advances in tissue engineering-related methodologies in order to provide a comprehensive volume that integrates a wide spectrum of methods. Written in the format of the highly successful Methods in Molecular Medicine™ series, each chapter seeks to drive tissue engineering into a clinical reality with step-by-step laboratory protocols, lists of necessary materials, and tips on troubleshooting and avoiding known pitfalls. Thorough and timely, Tissue Engineering, 2nd Edition is an invaluable resource for all scientists leading the way toward the first successful implantation of a fully functional artificial organ.